Social Support, Family Communication Patterns, Coping Strategies, and Quarter-Life Crisis among Fresh Graduates - Adisa Salsabilla Putri Darmawan; Tin Herawati; Defina (Universitas Ahmad Dahlan, 2026)
The transition to adulthood posed significant psychological and social challenges for fresh graduates, increasing vulnerability to quarter-life crisis. This study aims to examine the associations among social support, family communication patterns, coping strategies, and quarter-life crisis among fresh graduates. A quantitative cross-sectional survey was conducted with 411 fresh graduates selected through purposive sampling. Data were collected through an online questionnaire and analyzed using descriptive and inferential statistics, including independent sample tests and structural equation modeling. The results indicate that social support, family communication patterns, and coping strategies are negatively related to quarter-life crisis. Social support was indirectly associated with quarter-life crisis through family communication patterns. Family communication emerged as the strongest relational factor associated with quarter-life crisis, while coping strategies did not show a significant direct association. These findings highlighted the importance of family and social contexts in supporting psychological adjustment during early adulthood.